Side Jobs pada Mahasiswa Aktif Pendidikan Jasmani Kesehatan dan Rekreasi Fakultas Keguruan dan Ilmu Pendidikan - Fajar, Baihaki Padika; Gustiawati, Resty; Cahya, Dinda Mutiara; Anggraini, Citra; Saputro, Galeh; Rahmawati, Imel Emeli (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2025)
This research examines side jobs that can be undertaken by active physical education students. This research uses a survey method in the form of filling out a questionnaire using Google From media for students active in physical education, health and recreation. This research identifies various jobs that exist outside of lecture hours, the challenges they face, and the skills needed to succeed in this field. The research results show that physical education graduates have a variety of career choices, including becoming coaches, teachers and sports management. The results obtained from research using questionnaires via Google from media contained 23 samples, with the number of active students who had side jobs amounting to 65% and those who did not have side jobs amounting to 35%. Thus, most active students have side jobs outside of lecture hours because they want to gain experience before they enter the real world of work and also have daily living needs that must be met